Socio-Historical Development of the Nursing in the Culture of the People’s Republic of China - Ana Guzmán Aguilar; Brian Iván Barley López; Franklin Blanco Solano; María Fernanda Piedra Hernández; Keilor Steven Solórzano Taleno (Enfermería Actual de Costa Rica, 2013)
This essay presents a literature about some of the most remarkable origins of nursing in today's people’s Republic of China The main objectives around this topic were pursued to describe the socio-historical development of nursing in the culture of the people's Republic of China, specifically identify their origins as a discipline in the culture, to distinguish the influence of Chinese cultural patterns in the development of the nursing labor practice, and finally show the advance of nursing as a discipline from China vision against nowadays world vision. At the same time, for data collection sources were used journal articles on nursing, web pages about Chinese culture, reference books and an interview with a professional exmember of the Chinese government with extensive knowledge about this culture. Both the Foundation of Chinese philosophical tradition of Taoism and aesthetics in combination with western science will be important for future developments in nursing research and educational patterns of Chinese society, being altogether exemplary in terms of its development, expansion, planning and establishment in the general population. Henceforth was concluded that Chinese philosophies and religions have strongly influenced the way they live and think about the health and care within Chinese society